MYSTICISM AND THE SUPERNATURAL IN THE SHORT PROSE OF V. Y. BRYUSOV: THE BOUNDARIES OF THE REAL AND THE IRREGULAR - Nizomova Muslimabonu Ikromjon kizi (Bright Mind Publishing, 2025)
The article examines the features of the artistic embodiment of mysticism and the supernatural in the short prose of V. Ya. Bryusov. The methods of crossing the boundaries of the real and the unreal, manifested through images, plot twists and psychological states of the characters, are analyzed. Particular attention is paid to the role of the mystical as an aesthetic category, as well as the functioning of supernatural elements within the framework of the modernist poetics of the early twentieth century. The study is based on structural and intertextual analysis, as well as elements of psychoanalytic criticism. It is concluded that Bryusov consciously uses unreal components as a tool for philosophical understanding of reality and expanding the boundaries of world perception.
Keywords: Bryusov, short fiction, mysticism, supernatural, modernism, unreal, real, aesthetics, psychologism, artistic image.